My First Time to Touch a Cloud - Michaloudis, Ioannis (Moores Building Contemporary Art Gallery, 2012)
In our days, Climate Change and Greenhouse phenomenon are posing a crucial question: Will the sky continue to hang over humanity, or tomorrow our rainfather will disappear? A piece of sky in your hand could give you an answer. Also, handling a delicate fragment of blue sky (having a gold-hue shadow and a cloud inside it) will offer you more than one view on the matter. Nevertheless, the total of our interactive installation will not give you any echos, before it has sent an S.O.S (Save Our Sky) for Earth’s wounded atmosphere.